Ricardo Van Olston thesis - Van Olsten, Ricardo
Thesis entitled, "La cuarto dimension de la consciencia" ("The Fourth Dimension of Consciousness").
Collection material in Spanish.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Consciousness; Psychology -- Study and teaching